Integração financeira, fluxos de capitais, taxa de câmbio e crises financeiras nos países em desenvolvimento: teorias e evidências - Baptista, Livia Nalesso (2013)
The goal of this dissertation is to present an investigation of the theoretical and empirical relationship between financial integration, capital flows and the exchange rate, and between financial integration, capital flows and financial crises for developing countries. The theoretical literature analysis developed in Chapter 1 clarifies that there is no consensus regarding the hypothesis that financial integration and capital flows stimulate economic growth and consumption smoothing, also showing that there are channels through which they can lead to financial crises and appreciation of the exchange rate. Chapter 2 develops an econometric investigation regarding the relationship between financial integration, capital flows and the exchange rate, for a sample of 63 developing countries. The econometric results do not suggest that there is a statistically significant relationship between financial integration and exchange rate, and, therefore, they do not support the hypothesis that financial integration causes currency appreciation. Besides, the results suggest that capital flows cause appreciation of the exchange rate, and there are evidences that the effect of the capital flows over the exchange rate depends on the level of financial development, which means that the effect of appreciation is gradually attenuated by higher levels of financial development. Chapter 3 develops an econometric investigation regarding the relationship between financial integration, capital flows and financial crises, for a sample of 53 developing countries. The econometric results suggest that financial integration and capital flows do not raise the probability of financial crises.